Metallic iron or a Fe-based glassy alloy to reinforce aluminum: reactions at the interface during spark plasma sintering and mechanical properties of the composites - Dudina, Dina V.; Kvashnin, Vyacheslav I.; Bokhonov, Boris B.; Legan, Mikhail A.; Novoselov, Aleksey N.; Bespalko, Yuliya N.; Moreira Jorge, Alberto; Koga, Guilherme Y.; Ukhina, Arina V.; Shtertser, Alexandr A.; Anisimov, Alexander G.; Georgarakis, Konstantinos (MDPI, 2023)
The microstructural features and mechanical properties of composites formed by spark plasma sintering (SPS) of Al + 20 vol.% Fe and Al + 20 vol.% Fe66Cr10Nb5B19 (glassy alloy) mixtures composed of micrometer-sized particles are presented. The interaction between the mixture components was studied by differential thermal analysis and through examining the microstructure of composites sintered at two different SPS pressures. When the pressure was increased from 40 MPa to 80 MPa, the thickness of the reaction products formed between the iron particles and aluminum increased due to a more intimate contact between the phases established at a higher pressure. When the metallic glass was substituted for iron, the pressure increase had an opposite effect. It was concluded that local overheating at the interface in the case of Al + 20 vol.% Fe66Cr10Nb5B19 composites governed the formation of the product layers at 40 MPa. The influence of the nature of reinforcement on the mechanical properties of the composites was analyzed, for which sintered materials with similar microstructural features were compared. In composites without the reaction products and composites with thin layers of the products, the hardness increased by 13–38% relative to the unreinforced sintered aluminum, the glassy alloy and iron inclusions producing similar outcomes. The effect of the nature of added particles on the hardness and compressive strength of composites was seen when the microstructure of the material was such that an efficient load transfer mechanism was operative. This was possible upon the formation of thick layers of reaction products. Upon compression, the strong glassy cores experienced fracture, the composite with the glassy component showing a higher strength than the composite containing core-shell structures with metallic iron cores.
Keywords: metallic glass; reinforcement; aluminum; interface; spark plasma sintering; composite; microstructure; hardness; compressive strength